Empowering Rural Communities to Support the Development of Educational Tourism Through Organic Hydroponic Farming Training in Sido Mulio Village, Langkat - Hafnes Wahyuni (Journal of Saintech Transfer, 2026)
Sido Mulio Hamlet is a village with a lot of vacant land that can be used for hydroponic farming. This community service activity aims to increase the knowledge, skills, and empowerment of the community through training in organic hydroponic vegetable cultivation in support of the development of village edu-tourism. The activity was carried out from April to November 2025 using a participatory approach through the stages of socialization, training, production practice, mentoring, and evaluation. The method used was pre-experimental with measurements taken before and after training. Data were collected through questionnaires, observations, and focus group discussions, then analyzed descriptively. The results of the activity show a significant increase in community knowledge related to hydroponic cultivation, irrigation system installation, and plant nutrition management. This increase in knowledge contributes directly to improved practical skills and independent adoption of hydroponic technology. In addition, this activity has an impact on increasing the economic capacity of the community through the production of hydroponic vegetables and their use as a means of agricultural education. This activity confirms that practical organic- based hydroponic training supported by mentoring can have a real impact on community empowerment and the strengthening of community-based rural edutourism.